miR-590 promotes cell proliferation and invasion in T-cell acute lymphoblastic leukaemia by inhibiting RB1 - Miao, Mei-hua; Ji, Xue-qiang; Zhang, Hao; Xu, Jun; Zhu, Hong; Shao, Xue-jun (Oncotarget, 2016)
MicroRNAs play important roles in the pathogenesis of cancers by inhibiting gene expression at posttranscriptional level. Here, we identified that miR-590 and its predicted target gene RB1 are differentially expressed in T-cell acute lymphoblastic leukaemia (T-ALL). The correlation between miR-590 and RB1 was further confirmed in 395 T-ALL patients. In T-ALL cell lines, miR-590 promoted the cell proliferation by increasing G1/S transition. Moreover, migration and invasion assay showed that miR-590 promotes the migration and invasion of T-ALL cells by increasing E-cadherin and inhibiting MMP-9. Luciferase assays confirmed that miR-590 directly binds to the 3'untranslated region of RB1, and western blotting showed that miR-590 suppresses the expression of RB1 at the protein levels. This study indicated that miR-590 inhibits RB1 and promotes proliferation and invasion of T-ALL cells. Thus, miR-590 may represent a potential therapeutic target for T-ALL intervention.